Sistem Penunjang Keputusan Pemilihan Motif Kain Kaos Clothing Menggunakan Metode Analythical Hierarchy Process (AHP) - Zulistyaningsih, Ninda; Aditya, Addin; Sugiharto, Indra (LPPM STIKI MALANG, 2020)
Clothing is a manufacturer that manufactures all their products by their label. The rapid growth of the clothing business today makes competition among the clothing business entrepreneurs very competitive. They must be able to produce a product that is easily accepted by consumers, especially young people today. In these circumstances require clothing entrepreneurs to work more professionally to remain competitive and survive. Fabric is an important thing in doing a t-shirt production process in the clothing business. Today there are a lot of t-shirt motifs, from the plain to the lines with a variety of colors. Clothing business entrepreneurs must be able to determine which t-shirts are the best and can be produced to produce a product that is favored by consumers. But in the selection of T-shirt motifs, most clothing entrepreneurs are still guessing without having a benchmark for T-shirt motifs that are needed to be produced. For that we need a system that can help clothing entrepreneurs to be able to determine the criteria for the motif of the t-shirt to be produced and the selection process will be easier and not waste a lot of time. In this case, a decision support system will be made that can facilitate business owners clothing in determining the choice of the best fabric motifs for his business. One method that can be used as a solution is the Analytical Hierarchy Process (AHP) Method because this method is suitable for multi-criteria decision making. In this problem there are several criteria needed, namely type of material, type of yarn, fabric pattern, absorbency quality, grade of fabric and user category. The existence of this research is expected to provide benefits to the clothing business owner, which can facilitate the recommendation of t-shirt motifs for their businesses.